Student attendance registration system using QR Code for tuition centre / Nur Farizah Ishak and Zulfikri Paidi - Ishak, Nur Farizah; Paidi, Zulfikri (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Systems for recording student attendance are important for managing and monitoring individuals inside organisations, such as educational institutions, in order to maximise students' academic performance. However, the majority of small organisation, including tuition centres, continue to use a manual attendance system. This system is prone to mistakes, and it can lead to fraud when students sign for absent classmates on the attendance list and disrupting the class. A web-based student attendance system that records attendance using QR Code was developed to address these problems. According to the survey being done, the developed system was able to automatically enter students' attendance records into the database with the proper student id and the web application's network performance did not go over the acceptable response time. Thus, utilizing QR Codes to quickly and accurately register student attendance data can lessen the administrative workload at tuition centre.